Numerical Simulation on Optimization of Center Segregation for 50CrMo Structural Alloy Steel - Gao Xiangzhou; Yang Shufeng; Li Jingshe; Liao Hang (High Temperature Materials and Processes, 2016)
To improve the center segregation of billet for 50CrMo structural alloy steel, a 3D numerical model of solidification and heat transfer process for continuous casting had been established. The influence law of continuous casting process parameters on the secondary dendrite arm spacing (SDAS) and equiaxed crystal ratio had been obtained. It was shown that reducing superheat and casting speed and increasing the secondary cooling intensity could decrease SDAS. Reducing any one of the three parameters could increase the equiaxed crystal ratio. Adjusting only secondary cooling intensity could not make the SDAS and equiaxed crystal ratio change in the desired direction, but regulating the other two parameters could supply this gap. After optimizing the continuous casting process parameters of 50CrMo billet, the defect of center segregation was solved basically.